Improvement in medical students’ knowledge on chronic pain assessment through integrative learning approaches: a randomized controlled trial - Soenarto, Ratna Farida; Sukmono, Besthadi; Findyartini, Ardi; Susilo, Astrid Pratidina (Frontiers in Pain Research, 2023)
Introduction This study aimed to compare the knowledge and skills of medical students in chronic pain assessment after being trained using the PQRST (P, provoke and palliate; Q, quality; R, region and radiation; S, severity; T, time) and ACT-UP (A, activity; C, coping; T, think; U, upset; P, people) mnemonics with those using only the PQRST mnemonic. Methods A double-blind, randomized controlled trial was conducted at the Faculty of Medicine, Universitas Indonesia, including forty students who participated in a simulation-based chronic pain assessment workshop. Pre- and post-test scores were used to assess participants’ knowledge. Two independent raters assessed the students’ skills. Results No significant differences in knowledge or skills were observed between the groups; however, a significant improvement in the post-test scores (85.71 [71.43–95.24]) compared to the pre-test scores (61.90 [25.87–90.48]) was observed. The students reported high satisfaction with the workshop. Conclusions Training with the PQRST and ACT-UP mnemonics is not better than training with the PQRST mnemonic alone in improving students’ knowledge and skills in chronic pain assessment. Nevertheless, this pain education workshop was beneficial for student learning. Learning of patient-oriented chronic pain assessment should be provided in a repetitive and integrative fashion using different approaches, such as lectures, demonstrations, simulations, and interactions with patients experiencing chronic pain. To conclude, mnemonics are helpful but not a primary learning tool.